Impacts of household coal and biomass combustion on indoor and ambient air quality in China: Current status and implication. - Li, Q.; Jiang, J.; Wang, S.; Rumchev, Krassi; Mead-Hunter, Ryan; Morawska, L.; Hao, J. (2016)
This review briefly introduces current status of indoor and ambient air pollution originating from household coal and biomass combustion in mainland China. Owing to low combustion efficiency, emissions of CO, PM2.5, black carbon (BC), and polycyclic aromatic hydrocarbons have significant adverse consequences for indoor and ambient air qualities, resulting in relative contributions of more than one-third in all anthropogenic emissions. Their contributions are higher in less economically developed regions, such as Guizhou (61% PM2.5, 80% BC), than that in more developed regions, such as Shanghai (4% PM2.5, 17% BC). Chimneys can reduce ~80% indoor PM2.5 level when burning dirty solid fuels, such as plant materials. Due to spending more time near stoves, housewives suffer much more (~2 times) PM2.5 than the adult men, especially in winter in northern China (~4 times). Improvement of stove combustion/thermal efficiencies and solid fuel quality are the two essential methods to reduce pollutant emissions. PM2.5 and BC emission factors (EFs) have been identified to increase with volatile matter content in traditional stove combustion. EFs of dirty fuels are two orders higher than that of clean ones. Switching to clean ones, such as semi-coke briquette, was identified to be a feasible path for reducing >90% PM2.5 and BC emissions. Otherwise, improvement of thermal and combustion efficiencies by using under-fire technology can reduce ~50% CO2, 87% NH3, and 80% PM2.5 and BC emissions regardless of volatile matter content in solid fuel. However, there are still some knowledge gaps, such as, inventory for the temporal impact of household combustion on air quality, statistic data for deployed clean solid fuels and advanced stoves, and the effect of socioeconomic development. Additionally, further technology research for reducing air pollution emissions is urgently needed, especially low cost and clean stove when burning any type of solid fuel. Furthermore, emission-abatement oriented policy should base on sound scientific evidence to significantly reduce pollutant emissions.